Performance analysis of security framework for software defined network architectures - K. A. Varun Kumar; D. Arivudainambi (International Journal of Advances in Applied Sciences, 2019)
Software defined data centers (SDDC) and software defined networking (SDN) are two emerging areas in the field of cloud data centers. SDN based centrally controlled services takes a global view of the entire cloud infrastructure between SDDC and SDN, whereas Network Function Virtualization (NFV) is widely used for providing virtual networking between host and Internet Service Providers (ISP’s). Some Application as a Service used in NFV data centers have a wide range in building security services like Virtual firewalls, Intrusion Detection System (IDS), load balancing, bandwidth allocation and management. In this paper, a novel security framework is proposed to combat SDDC and SDN based on NFV security features. The proposed framework consists of a Virtual firewall and an efficient bandwidth manager to handle multiple heterogeneous application requests from different ISPs. Real time data were taken from an experiment for a week and A new simulation based proof of concept is admitted in this paper for validation of the proposed framework which was deployed in real time SDNs using Mininet and POX controller.